THE EFFECT BETWEEN COD AND BANK TRANSFER PAYMENT METHODS ON CONSUMER SATISFACTION IN MAKING ONLINE PURCHASE TRANSACTIONS : A CASE STUDY OF FEB UNIMAL STUDENTS - -, Muhammad Fahminuddin; Samsul Bahri; Adnan; Halida Bahri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of Cash on Delivery (COD) and bank transfer payment methods on consumer satisfaction in online purchasing transactions among students of the Faculty of Economics and Business (FEB) at Malikussaleh University. The primary data for this research were obtained through questionnaires distributed to students who had previously made online purchases. The population consisted of 2,809 students, and using the Slovin formula with a 10% margin of error, a sample of 97 respondents was determined. This number was rounded up to 100 respondents for ease of analysis. The sampling technique used was purposive random sampling, with criteria including active student status and prior experience in online shopping. The results showed that both COD and bank transfer payment methods had a positive and significant effect on consumer satisfaction. The partial test results revealed a t-value of 9.033 for COD and 9.063 for bank transfer, both exceeding the t-table value of 1.660 with a significance level of 0.000, leading to the acceptance of hypotheses H1 and H2. The simultaneous test also confirmed that both independent variables together significantly affect consumer satisfaction, with an F-value of 713.640 and a significance level of 0.000. These findings indicate that the chosen payment method plays a crucial role in determining consumer satisfaction. COD tends to provide a higher sense of security, while bank transfers are perceived as faster and more efficient especially by students who are familiar with digital financial services.